Enhancing Mathematics Understanding through Teams-Games-Tournaments (TGT) at MIS Darul Hikmah Karangan - Dwi Kris Wati; Lilik Mufafikhah (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to enhance students' understanding and engagement in mathematics at MIS Darul Hikmah Karangan by applying the Teams-Games-Tournaments (TGT) method. The study explores the effectiveness of TGT, a cooperative learning approach that combines teamwork, competition, and motivation, in improving students' academic performance and attitudes toward mathematics. The research is conducted in two cycles, each involving planning, action, observation, and reflection stages. Data is collected through student assessments, observations, and interviews with both students and teachers. The results show that TGT significantly increased students' participation in mathematics lessons. Students, who were previously passive in class, became more engaged and motivated to solve problems and discuss mathematical concepts with their peers. The competitive aspect of TGT encouraged students to work collaboratively, while the tournament-style structure provided them with the opportunity to demonstrate their understanding in a supportive environment. This method not only improved their mathematical skills but also fostered positive attitudes toward learning mathematics. Moreover, the study highlights the importance of creating a dynamic and interactive learning environment. Teachers reported that the TGT approach helped reduce students' anxiety about mathematics, making them more confident and willing to tackle challenging problems. The overall impact on classroom dynamics was positive, with improved student-teacher and student-student interactions. This research suggests that implementing TGT in mathematics classrooms can effectively enhance student learning outcomes and foster a more cooperative and engaging classroom atmosphere. It provides valuable insights for educators looking to adopt innovative and interactive teaching strategies to improve students' academic achievement in mathematics.